Structural, magnetic, magneto-transport properties and Bean-Rodbell model simulation of disorder effects in Cr3+ substituted La0.67Ba0.33MnO3 nanocrystalline synthesized by modified Pechini method - Oumezzine, Marwene (2017)
Nanocrystalline powders (around 100 nm) of La0.67Ba0.33CrxMn1-xO3 (x <= 0.17) perovskites have been synthesized by the sol-gel based Pechini method at low temperatures. The structure, resistivity, magnetization, and magneto-transport properties were systematically investigated as a function of Cr doping. Rietveld refinement of fitted and observed X-ray diffractions patterns shows the formation of single-phase compositions with rhombohedral symmetry (space group R (3) over barc, no. 167). Magnetization measurements confirm a transition from a paramagnetic to ferromagnetic phase. An increase in resistivity and a decrease in the metal-semiconductor transition and Curie temperatures was observed as a consequence of Cr doping. A simple phenomenological model, describing the competition between the PM-semiconductor and FM-metallic phases, was used to elucidate the temperature dependence of the resistivity with and without an applied magnetic field, which agrees quantitatively with experimental observations. Moreover, upon Cr doping, the polaron activation energy was found to increase due to the localization of carriers. Based on the Bean-Rodbell model, we studied the chromium inducing disorder effects of second-order phase transition of the system La(0.67)Ba(0.33)CrxMn(1-x)O(3), which was confirmed by the eta parameter value (eta < 1). We applied the model to the magnetization data of the samples for x = 0.10 and x = 0.15. We showed excellent agreement between measurements and simulated data. The results account for the random replacement of Mn3+ by Cr3+, which induces more disorder in the system, resulting in an increase in the disorder parameter and the fluctuation of the spin.